Case Report: Vancomycin-Associated Tubulointerstitial Nephritis in Clinical Practice-Case Report and Review of Literature - Kannan, Lakshmi; Raj, Rishi (Frontiers in Medicine, 2022)
Nephrotoxicity is one of the major limiting factors for vancomycin use. The most common histological patterns of kidney injury are acute tubulointerstitial nephritis and acute tubular necrosis. Patients who develop acute tubulointerstitial nephritis are prone to develop acute kidney injury with vancomycin rechallenge and, in most cases, present alone or as a part of Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS). The purpose of the review study is to identify biopsy-proven vancomycin-associated tubulointerstitial nephritis in literature, determine possible underlying pathophysiology and identify the consequences of vancomycin rechallenge in such patients.